2014
DOI: 10.1152/ajpheart.00259.2014
|View full text |Cite
|
Sign up to set email alerts
|

ROCK-dependent ATP5D modulation contributes to the protection of notoginsenoside NR1 against ischemia-reperfusion-induced myocardial injury

Abstract: Cardiac ischemia-reperfusion (I/R) injury remains a challenge for clinicians, which initiates with energy metabolism disorder. The present study was designed to investigate the protective effect of notoginsenoside R1 (NR1) on I/R-induced cardiac injury and underlying mechanism. Male Sprague-Dawley rats were subjected to 30-min occlusion of the left coronary anterior descending artery followed by reperfusion with or without NR1 pretreatment (5 mg·kg(-1)·h(-1)). In vitro, H9c2 cells were cultured under oxygen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 36 publications
(50 reference statements)
5
72
1
Order By: Relevance
“…The combination of PNS and NEP1-40 showed no obvious synergistic effect. A recent study showed that one effective constituent of PNS, notoginsenoside NR1, prevents I/R-induced myocardial injury by inhibiting ROCK (He et al, 2014), suggesting that the effective constituent against ROCK2 in ischemic stroke might be notoginsenoside NR1. However, further studies are needed to confirm this hypothesis, as well as to determine the mechanisms of action of PNS on NgR1 and RhoA expression following cerebral ischemia injury.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of PNS and NEP1-40 showed no obvious synergistic effect. A recent study showed that one effective constituent of PNS, notoginsenoside NR1, prevents I/R-induced myocardial injury by inhibiting ROCK (He et al, 2014), suggesting that the effective constituent against ROCK2 in ischemic stroke might be notoginsenoside NR1. However, further studies are needed to confirm this hypothesis, as well as to determine the mechanisms of action of PNS on NgR1 and RhoA expression following cerebral ischemia injury.…”
Section: Discussionmentioning
confidence: 99%
“…ATPase is a multisubunit complex consisting of 15 subunits including ATP 5D in mammals, which integrate into two domains, F1 and Fo. ATPase is reported to respond to ischemia and reperfusion by changing the expression of subunit protein (s)45 leading to ATPase dysfunction. ATPase dysfunction may impose dual deleterious impacts on the tissue underwent I/R, which, on one hand, results in ATP depletion thus affects all the energy consuming processes in the cell, such as cell contraction and ion pumps, as well as triggers the production of reactive oxidative species, and disrupts the mitochondrial membrane potential (ΔΨm), on the other hand, is implicated in the progressing of apoptosis6.…”
mentioning
confidence: 99%
“…QiShenYiQi Pills ® (a compound Chinese medicine containing Rb1 as a major component) has proven able to regulate energy metabolism deficiency and expression of ATP 5D in cardiac I/R injury1213. Our previous study reported that notoginsenoside R1 (NR1) ameliorated I/R induced myocardial injury by regulating levels of ROCK1 and ATP5D, implying a likely link between RhoA signaling pathway and energy metabolism regulation4. However, it is so far unclear whether Rb1 can improve I/R-induced cardiac energy deficiency and, if yes, what is the role of RhoA signaling pathway in the process.…”
mentioning
confidence: 99%
“…Notoginsenoside R1 markedly ameliorated myocardial infarction, improved cardiac function and increased cell viability. More importantly, notoginsenoside R1 prevented energy metabolism abnormity both in in vivo and in vitro models, mainly by down-regulating the expression of Rho kinase (ROCK) and up-regulating the expression of the mitochondrial ATP synthase δ-subunit (63). All these results indicate that a variety of ginsenosides can improve energy metabolism and alleviate the degree of reperfusion injury.…”
Section: Improving Cardiac Energy Metabolismmentioning
confidence: 89%